2017
DOI: 10.1038/s41598-017-13368-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of Bifidobacterium breve strain A1 for preventing cognitive impairment in Alzheimer’s disease

Abstract: It has previously been shown that the consumption of probiotics may have beneficial effects not only on peripheral tissues but also on the central nervous system and behavior via the microbiota–gut–brain axis, raising the possibility that treatment with probiotics could be an effective therapeutic strategy for managing neurodegenerative disorders. In this study, we investigated the effects of oral administration of Bifidobacterium breve strain A1 (B. breve A1) on behavior and physiological processes in Alzheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
211
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(235 citation statements)
references
References 49 publications
(49 reference statements)
8
211
0
1
Order By: Relevance
“…) , which can augment inflammation level in the plasma and subsequently in CNS (Kobayashi et al . ). These data present a hypothesis that gut microbiomes have strong connections with the pathogenesis of AD and diminished microbiota diversity can trigger several pathologies in the brain such as inflammation, cerebrovascular degeneration, Aβ aggregation and tau pathology.…”
Section: The Changes In Gut Microbiome Composition In Neurodegeneratimentioning
confidence: 97%
See 3 more Smart Citations
“…) , which can augment inflammation level in the plasma and subsequently in CNS (Kobayashi et al . ). These data present a hypothesis that gut microbiomes have strong connections with the pathogenesis of AD and diminished microbiota diversity can trigger several pathologies in the brain such as inflammation, cerebrovascular degeneration, Aβ aggregation and tau pathology.…”
Section: The Changes In Gut Microbiome Composition In Neurodegeneratimentioning
confidence: 97%
“…In addition to this in vitro study, Kobayashi et al . () investigated the effect of acetate on behavioural and working memory deficits in an AD model induced by intracerebral Aβ 25‐35 injection and observed that behavioural deficits in the mice were ameliorated. Interestingly, the improvement in behavioural deficits with the administration of acetate was also observed upon orally administrating sonicated B. breve strain A1 ( B. breve A1) homogenate.…”
Section: Gut Metabolites and Aβ Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…Savignac et al [88] showed that 6 weeks feeding of B. breve 1205 strain resulted in positive effects on compulsive behaviour in marble burying test, anxiolytic effects in the elevated plus maze and reduced bodyweight gain in model mice, contributing to a general amelioration of anxiety and metabolism. Kobayashi et al [89] showed that oral administration of B. breve A1, isolated from feces of human infants, prevented cognitive decline in Alzheimer disease (AD) model mice, with a reduction of neural inflammation; they observed that the probiotic provided ameliorations in both working memory and long-term memory. Furthermore, they found an increase of plasma acetate levels after the probiotic treatment and the neural inflammation reduction can be considered as a consequence of this increase due to B. breve administration, since SCFAs have been shown to have immune modulatory functions in model mice [90].…”
Section: B Breve Applications: Effectiveness In In Vitro Studies Andmentioning
confidence: 99%